HP0031 A national survey of parents and grandparents with rheumatoid arthritis, ankylosing spondylitis and back pain: preliminary findings. (1st June 2001) - Grant, MI; Wright, CC; Cullen, LA; Foster, NE; Barlow, JH
Abstract : Background: Research interest in parents and grandparents with musculoskeletal conditions in relation to their experiences of childcare is growing. Objectives: To survey parents and grandparents with rheumatoid arthritis (RA), ankylosing spondylitis (AS) and back pain (BP), in the United Kingdom. Methods: 448 participants (280 BP, 106 AS, 62 RA) responded to a cross-sectional postal survey. Age range was 23 to 88 years, range of duration of symptoms was <1–58 years and the sample was made up of 280 parents and 168 grandparents. Participants were recruited via voluntary organisations and Rheumatology Clinics. The majority of participants with RA and BP were female. Data were analysed using SPSS and content analysis. Results: The most prevalent problems, with childcare, were keeping up with children (e.g. energy) (87%), playing games (74%), feeling guilty about not being able to carry out routine childcare activities (74%). Other problems included, dressing, talking to children about arthritis, lifting and holding children, social activities, walking children to school, preparing meals, bathing, disciplining children. Participants with RA had the highest prevalence of difficulties overall. Grandparents reported a lower prevalence of problems than parents. Pain (100%), fatigue (90%) and stiffness (96%) were felt to cause difficulties with childcare. Guilt (40%), anxiety (37%) and depression (34%) were also felt to be contributory factors. The majority of participants with AS and BP had not received any advice on childcare but a third of those with RA had. Advice was given by occupational therapists (17%), general practitioners (12%), physiotherapists (7%) and rheumatologists (3%). Conclusions: Parents and grandparents with RA, AS and BP experience a wide range of problems with childcare (both physical and psychosocial) and do not appear to be receiving appropriate advice. This may indicate a gap in service provision for this group.